Transcatheter aortic valve durability, predictors of bioprosthetic valve dysfunction, longer-term outcomes - a review - Šolc, Abigail Johanna; Línková, Hana; Toušek, Petr (Expert review of medical devices, 2024)
INTRODUCTION: Transcatheter aortic valve implantation (TAVI) is one of the most significant inventions in cardiology, as it provides a viable minimally invasive treatment option for patients with aortic stenosis, the most common valvular disease in the developed world and one with a poor prognosis when left untreated. Using data available to date, this review aims to discuss and identify possible predictors of TAVI valve durability - an essential requirement for the device's wide-spread use, especially in younger patients. AREAS COVERED: This article explores the main causes of bioprosthetic valve dysfunction (BVD) based on pathophysiology and available data, and reviews possible predictors of BVD including prosthesis-related, procedure-related, and patient-related factors. An emphasis is made on affectable predictors, which could potentially be targeted with prevention management and improve valve durability. A literature search of online medical databases was conducted using relevant key words and dates; significant clinical trials were identified. A brief overview of important randomized controlled trials with mid to long-term follow-up is included in this article. EXPERT OPINION: Identifying modifiable predictors of valve dysfunction presents an opportunity to enhance and predict valve durability - a necessity as patients with longer life-expectancies are being considered for the procedure.
Keywords: structural valve deterioration; Aortic Valve Stenosis; Transcatheter Aortic Valve Replacement; aortální chlopeň; calcification; aortální stenóza; výsledek terapie; bioprosthetic valve dysfunction; srdeční chlopně umělé; lidé; Bioprosthesis; Heart Valve Prosthesis; Aortic stenosis; bioprotézy; Treatment Outcome; transkatetrální implantace aortální chlopně; selhání protézy; predictors; Aortic Valve; transcatheter aortic valve implantation; durability; prevention; Prosthesis Failure; Humans